Produção e cinética de formação de nanoestruturas de α-Fe em ligas do tipo Nanoperm ativadas mecanicamente - Pereira, Rodrigo Dias (2008)
Nanostructured Fe84M9Cu1B6 alloys were produced by mechanosynthesis, using two different procedures (Serie I – sequential mixture of elemental powder or Serie II – mixture of all elemental powder). The amorphous phase type FeMCuB was dominantly obtained for the first procedure (Serie I), in the contrary, a-Fe(M) nanograins dispersed in an FeMCuB amorphous matrix were spontaneously produced by mechanosynthesis in samples of the serie II. The nanocrystalline material also was activated in the serie I using a temperature controlled annealing.The a-Fe (M) nanograins in both series I and II have sizes of grains, obtained by the Scherrer expression, of about 8 to 10 nm. Using the technique of exploratory differential calorimetry different aspects were studied: the kinetics of the processes of (I) the structural relaxation of the amorphous matrix produced by milling and of (ii) the amorphous to crystalline transformation of the amorphous phase and, (iii) the full crystallization of the materials produced by mechanosynthesis. The structural relaxation of the as-produced materials occurs around 500 K, independently of the refractory element (M), but its activation energy is in a range between 30 and 100 kJ /mol, which depends on the procedure (Series I or Series II) and also on the element refractory M (Zr, V, Nb). Considering, for example, the Fe84Zr9Cu1B6 alloy produced in the procedures of the series I and II, a reduction in the value of the peak temperature of the relaxation of approximately 3% was verified, but the energies of activation of the materials prepared in Series I and II are substantially different, respectively 96 and 31 kJ / mole for the Series I and II. The process of crystallization occurs in the range of temperature of 730 to 750 K for the first stage and with activation energy between 55 and 160 kJ /mol, while the second stage of IXcrystallization occurs between 636 and 939 K and with an activation energy between 105 and 330 kJ /mol, depending on the refractory element and the type of procedure for preparing the sample (Series I and Series II). The crystallization temperatures and activation energies, associated with the first and second crystallization stages, were found to be much lower for the milled alloys compared to corresponding melt-spun alloys, an effect associated with a larger number of defects induced by the mechanosynthesis process. Mössbauer spectroscopy was the technique used for a description of the microstructure of materials produced in series I and II. Three different regions were observed. The amorphous phases of the FeMCuB were characterized by containing distributions of magnetic fields with hyperfine peak around 20 T. Within the amorphous phases of the different matrixes, it was possible in some cases to determine regions rich and poor in Fe. Moreover the grain core of the a-Fe(M) nanograins have hyperfine magnetic fields around 33 T , While the atoms of Fe on the surfaces of the a-Fe (M) nanograins have a contribution in the distribution of hyperfine magnetic fields around 31 T. The hyperfine and magnetic properties of the amorphous Fe84M9Cu1B6 alloys produced in this thesis were comparable to those found in melt-spun alloys with similar composition.